Analisis Internet Network Performance Menggunakan Parameter Quality of Service Pada Jaringan STMIK IKMI Cirebon - Martanto; Dian Ade Kurnia; Fathurrohman; Irfan Ali; Yudhistira Arie Wijaya (Ikatan Ahli Informatika Indonesia, 2024)
The use of the internet for employees is a crucial need to support the completion of their work. STMIK IKMI Cirebon also provides internet facilities for its employees. However, the internet facilities provided are not yet optimal, as evidenced by frequent connection disruptions. This study aims to measure the performance of the internet connection at STMIK IKMI Cirebon. The method used is Quality of Service (QoS), which is a method to assess how well the installed network functions and its ability to define the attributes of the network services provided. QoS is necessary to calculate the parameters that determine the quality of an internet network. The steps in this study include recording network traffic using Wireshark, followed by calculating parameters such as bandwidth, packet loss, delay, throughput, and jitter. The study results indicate that during data upload from 08:00 to 12:05 at STMIK IKMI Cirebon, the throughput percentage achieved was 31% with an index of 1